Molecular and Cellular Advances in Endometriosis Research - Laganà, Antonio Simone (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Endometriosis is defined as the presence of endometrial-like endometrial cells, glands, and stroma outside the uterus, causing a strong inflammatory-like microenvironment in the affected tissue. The exact prevalence of endometriosis is unknown, but estimates range from 2%-10% of women of reproductive age to 50% of infertile women. The etiopathogenesis of endometriosis remains controversial-immune, hormonal, genetic, and epigenetic factors may all be involved, and several theories have been proposed to explain it.This book aims to summarize some of the most recent advancements in basic and translational science (immunology, cell biology, genetics, and epigenetics) in the field of endometriosis that may create new scenarios and change our perspective of the topic.